THE INFLUENCE OF LIFESTYLE AND LIVE STREAMING ON E-COMMERCE APPLICATION TOWARDS IMPULSIVE BUYING OF TIKTOK SHOP USERS AMONG BOARDING STUDENTS - Sambeta, Agrita Priti; Mangantar, Maryam; Rogi, Mirah (Universitas Sam Ratulangi, 2024)
The purpose of this study was to determine the effect of lifestyle and live streaming in e-commerce applications on impulse purchases for boarding students who are TikTok Shop users. This study uses a quantitative approach and multiple linear analysis is used to analyze the effect between the independent variable and the dependent variable. A sample of 100 respondents was taken from boarding students who have used or shopped at TikTok Shop. The results of this study are that the lifestyle variable has a significant positive effect on the impulse purchase variable, live streaming variable has a significant positive effect on the impulse purchase variable and both independent variables have a significant positive effect on the dependent variable. Keywords: Lifestyle, Live Streaming, Impulsive Buying